2022
DOI: 10.3390/pathogens11121521
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Influenza A Virus to Ensure the Translation of Viral mRNAs

Abstract: Viruses are obligatorily intracellular pathogens. To generate progeny virus particles, influenza A viruses (IAVs) have to divert the cellular machinery to ensure sufficient translation of viral mRNAs. To this end, several strategies have been exploited by IAVs, such as host gene shutoff, suppression of host innate immune responses, and selective translation of viral mRNAs. Various IAV proteins are responsible for host gene shutoff, e.g., NS1, PA-X, and RdRp, through inhibition of cellular gene transcription, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…Interestingly, the result also showed that the levels of overexpressed PYCR2 in cells were decreased with the time of viral infection, and that the expression of endogenous PYCR2 was dysregulated during infection. Multiple mechanisms have been proposed for reducing cellular protein expression during influenza A virus infection, such as viral NS1 protein suppresses cellular RNA export and viral PA-X protein degrades cellular RNA (reviewed by Li et al, 2022 ). Dysregulation of PYCR2 expression during influenza A virus infection remains further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the result also showed that the levels of overexpressed PYCR2 in cells were decreased with the time of viral infection, and that the expression of endogenous PYCR2 was dysregulated during infection. Multiple mechanisms have been proposed for reducing cellular protein expression during influenza A virus infection, such as viral NS1 protein suppresses cellular RNA export and viral PA-X protein degrades cellular RNA (reviewed by Li et al, 2022 ). Dysregulation of PYCR2 expression during influenza A virus infection remains further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus proteins have many functions, from ion channels (M2) to nuclear localization signals (NS2), and proteases. RNA synthesis of the influenza virus is accomplished by multiple RNA polymerases [ 113 ]. As mentioned above, IAV transcription takes place in the nucleus, and polymerase basic 1 (PB1) is the most important RdRp for IAV.…”
Section: Virus-targeting Antiviralsmentioning
confidence: 99%